Effects of intravenous immunoglobulin therapy on behavior deficits and functions in sepsis model - ARICIOĞLU, FEYZA (SPRINGEROPEN, 2015)
Background: We aim to demonstrate behavioral alterations in a sepsis model using intravenous (IV) immunoglobulin G (IgG) and immunoglobulins enriched with IgA and IgM (IgGAM). Methods: We divided 48 Wistar albino rats into five groups: control group, sham-operated group (only antibiotic treatment), cecal ligation and puncture (CLP) group (CLP plus antibiotic treatment), IgG group (250 mg/kg IV IgG) and IgGAM group (250 mg/kg IV IgGAM). Intravenous immunoglobulins were given 5 min after the CLP procedure. Experimental animals put into three behavioral tasks 10, 30 and 60 days after the surgery; to evaluate the locomotor activity, an open field test was performed, elevated plus maze test was used to measure anxiety levels, and depressive state was assessed by forced swimming test. The effects of therapy which were acquired from the results of these tests were used to estimate the behavioral changes after CLP. Results: The mortality rate of 50% in the septic rats decreased to 30 and 20% with the administration of IgG and IgGAM, respectively. Significant changes on locomotor activity and depressive-like behavior were reported in the sepsis group; on the other hand, the treatment with immunoglobulins reduced the symptoms. Treatment with immunoglobulins attenuated the sepsis-related anxiogenic-like responses. Behavioral alterations returned to normal on day 60 in all groups. Conclusions: Sepsis caused deterioration on behavioral parameters. Immunoglobulin treatments alleviated the symptoms of functional disturbances and caused early reversal of behavioral deficits in septic animals.
Keywords: Sepsis; Immunoglobulins; Cecal ligation and puncture; Plus maze test; Forced swimming test; Behavioral alteration; BLOOD-BRAIN-BARRIER; CECAL LIGATION; COGNITIVE IMPAIRMENT; RATS; MEMORY; INHIBITION; PARAMETERS; BREAKDOWN; REVERSES; STRESS